First-Principle Calculations of Half-Metallic Double Perovskite La2BB'O6 (B,B'= 3d transition metal) (Communications in Computational Physics, 2014)
In this paper, we present calculations based on density functional theory using generalized gradient approximation (GGA) in double perovskite structure La2BB'O6 (B,B′=3d transition metal) out of 45 ($C_2^{10}$) combinational possibilities. Considering 4 types of magnetic states, namely, ferromagnetic (FM), ferrimagnetic (FiM), antiferromagnetics (AF), and nonmagnetic (NM) with full structure optimization, 13 possible surviving, stable FM/FiM-HM materials containing 6 FM-HM materials (La2ScNiO6, La2CrCoO6, La2CrNiO6, La2VScO6, La2VZnO6, and La2VNiO6) and 7 FiM-HM materials (La2VFeO6, La2ZnCoO6, La2TiCoO6, La2CrZnO6, La2CrMnO6, La2ScFeO6, and La2TiMnO6) are found. Considering the correlation effect (GGA+U), there are 6 possible half-metallic stable, surviving (HM) materials containing 3 FM-HM materials (La2ScNiO6, La2CrCoO6, and La2CrNiO6) and 3 FiM-HM materials (La2VFeO6, La2ZnCoO6, and La2TiCoO6).